Exploration of the psychosocial issues associated with gastroparesis: a qualitative investigation. Issue 21 (23rd February 2017) - Woodhouse, Sally; Hebbard, Geoff; Knowles, Simon R
Abstract : Aims and objectives: To build on the understanding of how individuals experience gastroparesis, how gastroparesis impacts on their lives and how they adapt to living with gastroparesis. Background: Gastroparesis is a neurogastroenterological disorder associated with increased psychological distress and reduced quality of life. Research shows that gastroparesis poses a significant burden across many facets of life; however, less is known about how individuals cope and adapt to living with the condition. Design: The study employed an interpretive phenomenological approach with semistructured interviews and thematic analysis. Methods: Ten gastroparesis patients were interviewed over the telephone ( n  = 8), Skype ( n  = 1) or face‐to‐face ( n  = 1). All interviews were audio‐recorded and transcribed. Results: Key themes identified: (1) frustration, (2) identity and (3) coping and adaptation. Gastroparesis patients experience significant frustration around their diagnostic journey, being misunderstood and the burden of living with the illness. Patients differed in how they identified with the illness, and this appeared to be associated with adaptation and whether they remained socially engaged. Conclusions: Gastroparesis is associated with significant frustration and burden; however, some patients adapt to living with the condition more effectively than others. Identity appears to play an important role in this relationship. Support aimed at fostering a health‐focused and resilient identity may assist gastroparesis patients in adaptation. Relevance to clinical practice: The findings of this study can help nurses and other healthcare professionals better understand the experience of living with gastroparesis and the factors that help patients best adapt to living with the condition. Nurses can help promote resilience in patients by discussing the importance of being health‐focused rather than illness‐focused. Nurses can also support patients by helping them problem‐solve issues that may arise around social eating and remaining socially engaged.